COMPARATIVE ANALYSIS OF SEROLOGICAL AND MOLECULAR TRANSFUSION TRANSMISSIBLE INFECTIONS SCREENING - Tashkovska, Marija; Makarovska Bojadjieva, Tatjana; Velkova, Emilija; Ilijevska, Violeta Dejanova; Petkovic, Elena; Ristovska, Elena; Todorovski, Bojan; Babalj Veljanoski, Ivana; Stojchevska, Aleksandra (Journal of Morphological Sciences, 2025)
Introduction. Transfusion Transmissible Infections (TTIs) remain a major concern in ensuring the blood safety. Nucleic acid testing (NAT) improves detection by shortening the window period (WP) and identifying occult infections. This study aims to determine the significance of NAT through a comparative analysis of the chemiluminescent serological technique (CMIA) and the molecular technique (NAT).  Methods. This retrospective study analyzed TTI testing data from 167979 blood donations (93,390 donors) between 2022 and 2024. Screening included HBV DNA, HCV RNA, and HIV RNA (Procleix UltrioPlex E, Panther System) and serological markers (HBsAg, anti-HCV, anti-HIV/p24) using the Architect 2000 platform. Repeatedly seroreactive samples underwent confirmatory testing (HBsAg neutralization, HCV/HIV immunoblot), while NAT-reactive samples were individually tested using the Procleix Ultrio Elite discriminatory assay.  Results. Serological testing identified 237 (0.25%) confirmed TTI cases, while NAT detected 245 (0.26%), including 22 (0.023%) NAT-only positive cases. Among these, 21 were HBV DNA-positive/HBsAg-negative. Follow-up samples from 11 donors showed seroconversion in 7 (33.3%), while 4 (19.0%) were identified as potential occult HBV infections (OBI). One HIV NAT-only case was detected. The NAT yield was 1 per 4,245 donations, decreasing over time. Residual risk per 100,000 donations declined from 10.55 to 4.59 for HBV, while remaining low for HCV and HIV (0.12 in 2024).  Conclusion. NAT enhances blood safety by detecting early and occult infections missed by serology. The declining NAT yield and residual risk emphasize improved screening efficiency. Integrating NAT with serological methods is crucial for reducing transfusion-transmitted infections.   Keywords: NAT, blood safety, transfusion-transmissible infections, residual risk